Pemahaman dan Peran Guru Pendidikan Agama Protestan dan Katolik dalam Gerakan Ekumenisme di SMA atau SMK Negeri dan Swasta Umum - Subali, Yohanes; Pangestu, Yanuarius; Andhika, Leonardus (STFT Jakarta, Indonesia, 2025)
This research focuses on the ecumenical movement within the scope of public and private senior high schools (SMA/SMK) in Sleman Regency, Yogyakarta. The subjects of this research are Protestant and Catholic Religious Education teachers, identified as initiators of ecumenical encounters. The research topics explored include the teachers' understanding of ecumenism and their role in fostering it through collaboration with Christian and Catholic Spiritual organizations in their respective schools. Drawing on James Fowler's theory of faith development, the study also aimed to evaluate the extent to which this collaboration supports students' faith development in relation to their current stages. The study employed a quantitative data analysis method using questionnaire distribution. The results indicate that the teachers understand the ecumenical movement as a means of promoting brotherhood among Christian students, which is realized through joint activities. This ecumenical movement, while serving as a commendable model, must also be evaluated to achieve the ideal state of students' faith development. Their collaboration should provide a space for sharing experiences and mutual strengthening in the process of faith development toward maturity.